2011
DOI: 10.1258/jrsm.2011.110010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diseases influence major life changing decisions: a new domain in quality of life research

Abstract: SummaryThe purpose of this review is to identify knowledge about the influence of chronic disease on major life changing decisions (MLCDs). This review was carried out in three stages: identification of key search terms; selection of databases and searching parameters; and evaluation of references. Only two articles matched the main search term 'major life changing decisions'. No article reviewed or measured the influence of chronic disease on major life changing decisions. However, 76 articles and various sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 58 publications
0
52
0
3
Order By: Relevance
“…There are many published surveys assessing the impact of chronic diseases on patients' QoL. However, these studies have not addressed the long-term impact of chronic diseases on critical life decisions taken by patients [12]. …”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…There are many published surveys assessing the impact of chronic diseases on patients' QoL. However, these studies have not addressed the long-term impact of chronic diseases on critical life decisions taken by patients [12]. …”
Section: Quality Of Lifementioning
confidence: 99%
“…Even follow-up studies, which might be expected to encompass more long-term issues, usually compare current impacts before and after a given intervention. In the study by Bhatti et al [12], adult dermatology patients explained how their chronic disease had influenced major life-changing decisions. The authors evaluated 308 responses (mean age 51.8 years, mean disease duration 19 years).…”
Section: Quality Of Lifementioning
confidence: 99%
“…However disease may have an additional major long-term impact by influencing major life changing decisions (MLCDs) [1,2], such as those concerning education, career, relationships or having children [3-7]. …”
Section: Introductionmentioning
confidence: 99%
“…Bhatti et al (2011) reported about the impact of chronic diseases on major life changing decisions like marriage, divorce, childbearing etc. It is suggested that the poor health from a spouse at a young age may cause marriage breakup over time.…”
Section: Partnershipmentioning
confidence: 99%
“…It is suggested that the poor health from a spouse at a young age may cause marriage breakup over time. For a couple with early stage disease and the option of fertility sparing surgery, the decision to intend to have a child is difficult due to the fear of recurrence (Bhatti et al 2011). Glantz et al (2009) described that the risk of being abandoned by the partner after surviving a severe disease is especially higher for women (20.8%) than for men (2.9%).…”
Section: Partnershipmentioning
confidence: 99%